Evaluation of level 2 oncoplastic breast surgery outcomes in patients of reproductive age using the BREAST-Q: A comparative analysis - Ozgul, Halit; Cakir, Remzi Can; Celik, Omer; Yur, Mesut (Elsevier B.V., 2025)
Background and objectives: Oncoplastic breast surgery (OBS) is an alternative to breast-conserving surgery (BCS) aimed at enhancing aesthetic and functional outcomes following breast cancer surgery. This study aimed to evaluate the potential benefits of OBS over BCS in terms of satisfaction with breasts, psychosocial well-being, and sexual well-being using patient-reported outcome measures. Methods: Data from patients treated with OBS (n = 93) and BCS (n = 138) between January 1, 2021, and December 31, 2023, were collected from the treatment records and patient files of a training and research hospital. The patients completed the BREAST-Q questionnaire, and the patient-reported outcomes were compared between the OBS and BCS groups. Results: Satisfaction with breasts was 90 % (82–96 %) in the OBS group compared to 66 % (58–72 %) in the BCS group, which revealed a statistically significant difference (p < 0.001). Psychosocial well-being was 88 % (80–96 %) in the OBS group versus 65.5 % (56–72 %) in the BCS group, indicating a statistically significant difference (p < 0.001). Sexual well-being was 82 % (78–94) in the OBS group and 62 % (56–72) in the BCS group, which was also statistically significant (p < 0.001). Conclusion: This study demonstrated that patients treated with OBS reported better outcomes on the BREAST-Q compared to those treated with BCS. © 2025 Formosan Medical Association
Keywords: Breast cancer; Breast-conserving surgery; BREAST-Q; Oncoplastic breast surgery; Patient-reported outcomes